'Bicycles are really important for women!' Exploring bicycles, gender and development in Nicaragua and Uganda. Issue 2 (1st February 2022) - Hayhurst, Lyndsay M. C.; McSweeney, Mitchell; Otte, Janet; Bandoles, Emerald; Cruz Centeno, Lidieth del Socorro; Wilson, Brian
Abstract: This article explores 'bicycles for development' (BFD) – a 'movement' that positions the bicycle as a tool to promote key development goals, especially those related to the achievement of gender equality. Despite the increasing growth and prominence of BFD, there remains limited empirical research that investigates the intersections among gender, development, mobility and technologies such as the bicycle. Using visual participatory action research – informed by postcolonial feminist theory and new materialisms – this study explored how bicycles shaped the lives of women and girls in both structured BFD programmes (Uganda) and recreational cycling environments (Nicaragua). Three interrelated themes are discussed: (1) within communities there are conflicting views of the women and girls who participate in BFD and broader cycling related activities; (2) women in this study, through their involvement in BFD programmes or their engagement in cycling, challenge gender norms and resist traditional gender stereotypes related to cycling; and (3) access to a bicycle is associated with a focus on domestic and income-generating work – (re-)producing the burden on women to be primary caregivers. We conclude by reflecting on the duality of the bicycle as a promising and intricate technology used to contribute to gender and development objectives.